2013
DOI: 10.1111/anae.12175
|View full text |Cite
|
Sign up to set email alerts
|

Nasotracheal intubation with three indirect laryngoscopes assisted by standard or modified Magill forceps

Abstract: We assessed the effect of modifying standard Magill forceps on the laryngeal introduction of an Eschmann stylet during nasotracheal intubations with three indirect laryngoscopes (Airtraq™, C-MAC(®) or GlideScope(®)) in patients with predicted difficult intubation. We allocated 50 participants to each laryngoscope. The stylet was advanced by one forceps followed by the other (standard or modified), with each sequence allocated to 25/50 for each laryngoscope. There were no differences in rates of failed tracheal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 22 publications
1
33
0
Order By: Relevance
“…Furthermore, the Trachway stylet tip can be positioned proximal to the side hole of the nasotracheal tube in order that its softened tip prevents the stylet from damaging surrounding tissues. Trachway-assisted nasotracheal intubation easily facilitates tube tip advancement into the trachea by its levering effect and does not require accessory tools such as Magill forceps [18] or cuff inflation [7]. The scope-first technique that we used for fibreoptic intubation was superior to a tube-first technique because tube advancement through the nasopharynx prevents the insertion cord tip from being misplaced into the Murphy eye of the tracheal tube [19].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the Trachway stylet tip can be positioned proximal to the side hole of the nasotracheal tube in order that its softened tip prevents the stylet from damaging surrounding tissues. Trachway-assisted nasotracheal intubation easily facilitates tube tip advancement into the trachea by its levering effect and does not require accessory tools such as Magill forceps [18] or cuff inflation [7]. The scope-first technique that we used for fibreoptic intubation was superior to a tube-first technique because tube advancement through the nasopharynx prevents the insertion cord tip from being misplaced into the Murphy eye of the tracheal tube [19].…”
Section: Discussionmentioning
confidence: 99%
“…That would indicate that video laryngoscopes are a useful investment. Staar et al published a paper in which they compared the ease of oral intubation using the GlideScope® classic, the Airtraq™ and the C-Mac, a Macintosh-like blade with an integrated camera, in patients with predicted difficult airways [16]. The authors found no difference in the success rates for oral intubation.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies are available in literature for atraumatic intubation like use of NGT, wendl tube, urethral catheter, esophageal stethoscope or red rubber tube. [3][4][5] In our case nasotracheal intubation was the only option as oral cavity was inaccessible for intubation and NGT guided technique was advantageous because while a preformed tracheal tube passed through the nasopharynx, nasogastric tube acted as a guide for lower pathway (relatively avascular area). After retrieving the NGT, the tube was easily advanced through the laryngeal inlet with the help of a fibrooptic bronchoscope as further blind intubation could impinge on the laryngeal inlet or at arytenoids cartilage and could cause traumatic bleed.…”
Section: Introductionmentioning
confidence: 99%